Database preservation toolkit: state-of-the-art and future plans in the context of the E-ARK project - Silva, Hélder (2015)
The project is co-funded by the European Commission under the ICT Policy Support Programme within Call 7 of the Competitiveness and Innovation Framework Programme (Grant agreement no: 620998). KEEP SOLUTIONS is also a co-funder of this work